An epoxy anti-corrosion coating and its preparation method

By hydroxylation and modification of boron nitride and adding it to epoxy anticorrosion coatings, the problems of voids and lack of long-term anticorrosion properties of existing epoxy anticorrosion coatings are solved, and the coating is highly corrosion-resistant and hydrophobicity.

CN117511336BActive Publication Date: 2025-02-11GUANGDONG PAINT COLOR NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311501032.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2025-02-11
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

The existing epoxy anticorrosion coatings have limited their application due to the uneven volatility and curing of diluents and the lack of long-term anticorrosion properties.

Method used

Boron nitride is hydroxylated with high concentration alkali liquid, and modified with silane coupling agent and catechol derivatives, and added to epoxy anticorrosion coatings to form the reasonableness of modified boron nitride and other components. Compatibility to improve the hydrophobicity and corrosion resistance of the coating.

Benefits of technology

The corrosion resistance and hydrophobicity of the coating are significantly improved, water penetration is prevented and a stable passivation film is formed, and the corrosion resistance of the coating is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004544276190000091
    Figure BDA0004544276190000091
  • Figure BDA0004544276190000092
    Figure BDA0004544276190000092
  • Figure BDA0004544276190000101
    Figure BDA0004544276190000101
Patent Text Reader

Abstract

The present invention discloses an epoxy anticorrosive coating and a preparation method thereof, wherein the coating comprises the following raw materials by weight: 30 to 50 parts of epoxy resin; 25 to 40 parts of inorganic pigments and fillers; 5 to 10 parts of curing agent; 1 to 5 parts of boron nitride or modified boron nitride; 0.01 to 0.2 parts of defoaming agent; and 0.01 to 0.2 parts of leveling agent. The present invention uses a relatively high concentration of alkali solution to perform hydroxylation on boron nitride, and then uses a silane coupling agent and a catechol derivative to further modify the boron nitride to obtain a modified boron nitride, which is added to the epoxy anticorrosive coating and has a reasonable compatibility with other components. After forming the coating, the hydrophobicity of the surface is improved, so that it is difficult for water to penetrate into the coating, and the catechol group also forms a stable passivation film, which significantly improves the corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of epoxy anti-corrosion coatings, and in particular to an epoxy anti-corrosion coating and a preparation method thereof. Background Art

[0002] Epoxy anti-corrosion coating is a highly efficient anti-corrosion coating, usually composed of epoxy resin, curing agent, filler and solvent. Epoxy anti-corrosion coating has strong chemical stability and corrosion resistance, and can effectively prevent the corrosion of metal structures in harsh environments such as strong acid, weak alkali, caustic substances and seawater. It is also a wear-resistant, pressure-resistant, heat-resistant and impact-resistant coating, and is widely used in coating protection in the fields of ships, marine facilities, chemical equipment, petrochemicals, railway bridges, etc. The existing epoxy anti-corrosion coatings inevitably have gaps due to the volatilization of diluents and uneven curing, as well as lack of long-term anti-corrosion performance, which greatly hinders the application of epoxy anti-corrosion coatings.

[0003] Studies have shown that the introduction of nanomaterials into epoxy anticorrosion coatings is a successful strategy to improve the anticorrosion performance of coatings and give coatings different functions. This is due to the enhanced barrier properties and higher connection density of composite coatings with nanomaterials, which show excellent long-term anticorrosion performance. For example, CN111363450A discloses a modified epoxy anticorrosion coating and its preparation method and application, including 5-30 parts of epoxy resin; 2-10 parts of MOFs-carbon nanotube-graphene composite nanomaterials; 10-45 parts of pigments and fillers; 5-20 parts of curing agent; 2-8 parts of auxiliary agent; 2-10 parts of water, carbon nanotubes connect MOFs and pass through and disperse with graphene between graphene sheets to form a multi-dimensional network structure, and the obtained modified epoxy anticorrosion coating has better corrosion resistance and mechanical strength. However, the preparation process of MOFs is cumbersome and the raw materials used are expensive.

[0004] Therefore, there is still a need to provide a simple, low-cost epoxy anti-corrosion coating that provides significant performance. Summary of the invention

[0005] In order to solve the technical problems existing in the prior art, the present invention provides an epoxy anti-corrosion coating, which comprises the following raw materials in parts by weight:

[0006] 30-50 parts of epoxy resin; 25-40 parts of inorganic pigments and fillers; 5-10 parts of curing agent; 1-5 parts of boron nitride or modified boron nitride; 0.01-0.2 parts of defoaming agent; 0.01-0.2 parts of leveling agent.

[0007] Furthermore, the inorganic pigment filler is barium sulfate; the curing agent is a phenolic amine epoxy curing agent; the defoaming agent is an organosilicon defoaming agent; and the leveling agent is an organosilicon leveling agent.

[0008] Generally speaking, the main components of epoxy anticorrosion coatings include epoxy resin, curing agent and inorganic pigments and fillers, etc. Among them, epoxy resin is the main component of the coating, which is used to provide the coating with viscosity, wear resistance and corrosion resistance, curing agent is used to enhance the hardness and chemical resistance of the coating, and inorganic pigments and fillers can be used to adjust the performance of the coating and reduce costs.

[0009] Boron nitride is a layered material composed of covalently bonded nitrogen and boron. It has mechanical strength, flexibility, good thermal conductivity, excellent chemical stability, and due to its high electrical insulation properties, it can provide effective corrosion protection in coatings without forming a galvanic cell with the underlying metal. However, the application of boron nitride is highly limited due to its poor dispersion properties. In addition, there are few functional groups or active sites in the boron nitride structure that can be used for bonding modification. Treating boron nitride with a high concentration of alkali can make its surface hydroxylated and easily modified with silane coupling agents for hydrophobicity. Catechol groups and Fe 3+ The formation of complexes produces a strong passivation effect, thereby enhancing the corrosion resistance of the coating. The use of catechol derivatives Urushiol not only carries a catechol group but also has a longer carbon chain, which may further improve the corrosion resistance and hydrophobicity.

[0010] Furthermore, the preparation method of the modified boron nitride comprises:

[0011] Dispersing boron nitride in an alkali solution and stirring to react, and then collecting insoluble matter;

[0012] The insoluble matter, the silane coupling agent and the catechol derivative are dispersed in an oily organic solvent and stirred for reaction to obtain modified boron nitride.

[0013] Further, the concentration of the alkali solution is 5 to 10 mol / L, and the alkali solution can be a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution or an ammonia aqueous solution;

[0014] The mass ratio of boron nitride to alkali solution is 2-5:50-100.

[0015] Furthermore, the mass ratio of the insoluble matter, the silane coupling agent, the catechol derivative and the oily organic solvent is 1-2: 0.2-0.5: 0.1-0.2: 50-100.

[0016] Further, the silane coupling agent is at least one of KH550, KH560, KH570, KH792 or DL602;

[0017] Furthermore, the oily organic solvent is at least one of toluene or xylene.

[0018] Furthermore, the catechol derivative is urushiol.

[0019] Furthermore, the stirring reaction is carried out at a temperature of 60 to 100° C. and for a time of 5 to 24 hours.

[0020] The present invention also provides a method for preparing the above-mentioned epoxy anticorrosive coating, which is characterized by comprising:

[0021] The boron nitride or modified boron nitride, epoxy resin and inorganic pigments and fillers are mixed to obtain a prefabricated coating;

[0022] The prefabricated coating, curing agent, defoaming agent and leveling agent are mixed and then degassed to obtain the epoxy anticorrosive coating.

[0023] Furthermore, the degassing is carried out in a constant temperature vacuum oven.

[0024] The present invention also provides the use of the above-mentioned epoxy anti-corrosion coating in the surface coating of metal materials

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention uses a relatively high concentration of alkali solution to perform hydroxylation treatment on boron nitride, and then uses a silane coupling agent and a catechol derivative to further modify the boron nitride to obtain a modified boron nitride, which is added to an epoxy anticorrosive coating in a reasonable compatibility with other components. After the coating is formed, the hydrophobicity of the surface is improved, thereby making it difficult for water to penetrate into the interior of the coating, and the catechol group also forms a stable passivation film, which significantly improves the corrosion resistance. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0028] Description of some raw materials used in the examples of the present invention:

[0029] Epoxy resin, E44, was purchased from Wanqing Chemical Technology Co., Ltd.;

[0030] Boron nitride, purchased from Hubei Kewode Chemical Co., Ltd., particle size 1-19 μm;

[0031] Barium sulfate was purchased from Shenzhen Huasenda Metal Materials Co., Ltd.;

[0032] Phenolic amine epoxy curing agent, brand CYDHD-531, purchased from Baling Petrochemical;

[0033] Silicone defoamer, brand DF-2872, purchased from Dongguan Defeng Defoamer Co., Ltd.;

[0034] The silicone leveling agent, brand BYK-333, was purchased from BYK Chemical Company of Germany.

[0035] Other raw materials not mentioned are common raw materials in the art and can be purchased and used directly.

[0036] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0039] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1.5 kg of boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0040] Step 2, mechanically stirring boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0041] Step 3: The prefabricated coating, phenolic amine epoxy curing agent, silicone defoaming agent and silicone leveling agent were mechanically stirred at 200 rpm for 20 min and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 min to obtain an epoxy anticorrosive coating.

[0042] Example 2

[0043] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0044] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 0.5 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0045] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0046] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0047] Wherein, the preparation method of modified boron nitride is:

[0048] (1) At 25° C., 0.3 kg of boron nitride was mixed with 15 kg of a 5 mol / L sodium hydroxide aqueous solution, and then the temperature was raised to 90° C. and stirred for reaction for 12 h, and then naturally cooled to 25° C., filtered, washed, and dried to obtain an insoluble matter;

[0049] (2) At 25°C, 0.2 kg of insoluble matter, 0.02 kg of KH550, 0.01 kg of urushiol and 5 kg of toluene were mixed, then heated to 80°C and stirred for reaction for 6 hours, then naturally cooled to 25°C, filtered, washed and dried to obtain modified boron nitride.

[0050] Example 3

[0051] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0052] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0053] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0054] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0055] Wherein, the preparation method of modified boron nitride is the same as that in Example 2.

[0056] Example 4

[0057] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0058] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1.5 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0059] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0060] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0061] Wherein, the preparation method of modified boron nitride is the same as that in Example 2.

[0062] Example 5

[0063] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0064] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 2 kg of modified boron nitride, 0.1 kg of silicone defoamer and 0.1 kg of silicone leveling agent;

[0065] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0066] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0067] Wherein, the preparation method of modified boron nitride is the same as that in Example 2.

[0068] Comparative Example 1

[0069] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0070] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1.5 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0071] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0072] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0073] Wherein, the preparation method of modified boron nitride is:

[0074] At 25°C, 0.2 kg of boron nitride, 0.02 kg of KH550, 0.01 kg of urushiol and 5 kg of toluene were mixed, then heated to 80°C and stirred for reaction for 6 hours, then naturally cooled to 25°C, filtered, washed and dried to obtain modified boron nitride.

[0075] Comparative Example 2

[0076] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0077] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1.5 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0078] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0079] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0080] Wherein, the preparation method of modified boron nitride is:

[0081] (1) At 25° C., 0.3 kg of boron nitride was mixed with 15 kg of a 5 mol / L sodium hydroxide aqueous solution, and then the temperature was raised to 90° C. and stirred for reaction for 12 h, and then naturally cooled to 25° C., filtered, washed, and dried to obtain an insoluble matter;

[0082] (2) At 25°C, 0.2 kg of insoluble matter, 0.03 kg of KH550 and 5 kg of toluene were mixed, then heated to 80°C and stirred for reaction for 6 hours, then naturally cooled to 25°C, filtered, washed and dried to obtain modified boron nitride.

[0083] Comparative Example 3

[0084] A method for preparing an epoxy anticorrosive coating comprises the following steps:

[0085] Step 1, weighing 50 kg of epoxy resin E44, 30 kg of barium sulfate, 8 kg of phenolic amine epoxy curing agent, 1.5 kg of modified boron nitride, 0.1 kg of organosilicon defoamer and 0.1 kg of organosilicon leveling agent;

[0086] Step 2, mechanically stirring the modified boron nitride, epoxy resin E44 and barium sulfate at 300 rpm for 30 minutes to obtain a prefabricated coating;

[0087] Step 3, the prefabricated coating, phenolic amine epoxy curing agent, silicone defoamer and silicone leveling agent are mechanically stirred at 200 rpm for 20 minutes and then transferred to a constant temperature vacuum oven at 60° C. for degassing for 30 minutes to obtain an epoxy anticorrosive coating;

[0088] Wherein, the preparation method of modified boron nitride is:

[0089] (1) At 25° C., 0.3 kg of boron nitride was mixed with 15 kg of a 5 mol / L sodium hydroxide aqueous solution, and then the temperature was raised to 90° C. and stirred for reaction for 12 h, and then naturally cooled to 25° C., filtered, washed, and dried to obtain an insoluble matter;

[0090] (2) At 25°C, 0.2 kg of insoluble matter, 0.03 kg of urushiol and 5 kg of toluene were mixed, then heated to 80°C and stirred for reaction for 6 hours, then naturally cooled to 25°C, filtered, washed and dried to obtain modified boron nitride.

[0091] Test Case

[0092] The epoxy anticorrosive coatings prepared in the above embodiments and comparative examples of the present invention were spin-coated on Q235 stainless steel with a length, width and height of 5cm×5cm×1mm respectively, first cured at room temperature of 25°C for 12h, then transferred to a constant temperature oven at 60°C for curing for 12h, and the final coating thickness was about 100μm. The stainless steel with the coating was used as a working electrode. Metal coatings often need to be in direct contact with water. The stronger the hydrophobicity of the coating, the easier it is to inhibit water from penetrating into the underlying metal. Table 1 shows the water contact angles of the embodiments and comparative examples.

[0093] Table 1 Water contact angles of Examples and Comparative Examples

[0094] Water contact angle (°) Example 1 129.4 Example 2 143.5 Example 3 147.8 Example 4 150.1 Example 5 148.1 Comparative Example 1 135.6 Comparative Example 2 144.3 Comparative Example 3 142.5

[0095] From the test results of Table 1, it can be seen that Example 1 has the smallest water contact angle, which may be caused by the poor dispersibility of boron nitride in the coating. From Comparative Examples 2 and 3, it can be seen that the modification of hydroxylated boron nitride with KH550 or urushiol can improve the surface properties of boron nitride and improve its dispersibility. Comparative Example 1 is a boron nitride that has not been treated with alkali solution. Although boron nitride is modified with KH550 and urushiol, its water contact angle is not significantly improved. From the results of Examples 2 to 5, it can be seen that with the increase in the addition amount of modified boron nitride (modification of hydroxylated boron nitride by KH550 and urushiol), the water contact angle first increases and then decreases. Among them, Example 4 has a maximum value of 150.1° and reaches the super-hydrophobic level. These results show that the modification of hydroxylated boron nitride by KH550 and urushiol can improve its dispersibility in epoxy resin, and the use of a suitable ratio can reach the super-hydrophobic level.

[0096] The test was carried out on an electrochemical workstation using a conventional three-electrode system, wherein the reference electrode was a saturated calomel electrode, the counter electrode was a platinum sheet electrode, and the electrolyte was a 3.5 wt % NaCl aqueous solution.

[0097] The open circuit potential helps predict how a material will participate in the electrochemical corrosion reaction in the medium. Its monitoring is particularly important for metal corrosion. These working electrodes were immersed in a 3.5wt% NaCl aqueous solution and their open circuit potentials were continuously monitored. The results are shown in Table 2.

[0098] Table 2 Open circuit potential results

[0099]

[0100] From the results in Table 2, it can be seen that the open circuit potential of each working electrode decreases with the increase of immersion time. It can also be seen that Example 4 has the highest open circuit potential after 600 hours of immersion, indicating that the corrosion resistance of the coating is the strongest under this condition.

[0101] The corrosion performance was tested by electrochemical impedance spectroscopy after the open circuit potential of the working electrode in the electrolyte was stabilized. The test frequency range was set to 10 -2 ~10 5 Hz, and the amplitude of the AC voltage was 20 mV. The AC impedance of the working electrode after immersion for 60 days was tested, and the charge transfer resistance results are shown in Table 3.

[0102] Table 3 AC impedance results

[0103]

[0104]

[0105] The charge transfer resistance is inversely proportional to the corrosion rate. The results in Table 3 also show that the epoxy anti-corrosion coating obtained in Example 4 has the best corrosion resistance.

[0106] In summary, the present invention uses a relatively high concentration of alkali solution to perform hydroxylation on boron nitride, and then uses a silane coupling agent and a catechol derivative to further modify the boron nitride to obtain a modified boron nitride, which is added to the epoxy anti-corrosion coating in a reasonable compatibility with other components. After the coating is formed, the hydrophobicity of the surface is improved, thereby making it difficult for water to penetrate into the interior of the coating. The catechol group also forms a stable passivation film, which significantly improves the corrosion resistance.

[0107] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An epoxy anticorrosive coating, characterized in that: The following raw materials are included in parts by weight: Epoxy resin 30-50 parts; inorganic pigments and fillers 25-40 parts; curing agent 5-10 parts; modified boron nitride 1-5 parts; defoaming agent 0.01-0.2 parts; Leveling agent 0.01~0.2 parts; The preparation method of the modified boron nitride comprises: Dispersing boron nitride in an alkali solution and stirring to react, and then collecting insoluble matter; Dispersing the insoluble matter, the silane coupling agent and the catechol derivative in an oily organic solvent and stirring to react to obtain modified boron nitride; The concentration of the alkali solution is 5-10 mol / L; The mass ratio of boron nitride to alkali solution is 2~5:50~100; The mass ratio of the insoluble matter, the silane coupling agent, the catechol derivative and the oily organic solvent is 1-2: 0.2-0.5: 0.1-0.2: 50-100; The catechol derivative is urushiol; The silane coupling agent is KH550.

2. The epoxy anticorrosive coating according to claim 1, characterized in that: The oily organic solvent is at least one of toluene and xylene.

3. The epoxy anticorrosive coating according to claim 1, characterized in that: The inorganic pigment filler is barium sulfate; the curing agent is a phenolic amine epoxy curing agent; the defoaming agent is an organosilicon defoaming agent; and the leveling agent is an organosilicon leveling agent.

4. A method for preparing the epoxy anticorrosive coating according to any one of claims 1 to 3, characterized in that: include, The modified boron nitride, epoxy resin and inorganic pigments and fillers are mixed to obtain a prefabricated coating; The prefabricated coating, curing agent, defoaming agent and leveling agent are mixed and then degassed to obtain the epoxy anticorrosive coating.

5. Use of the epoxy anticorrosion coating as claimed in any one of claims 1 to 3 in surface coating of metal materials.

Citation Information

Patent Citations

  • Modified epoxy anticorrosive coating, and preparation method and application thereof

    CN111363450A

  • Preparation method of catechol-grafted boron nitride modified resin composite material

    CN112391032A

  • Dual-modified waterborne epoxy resin anticorrosive paint and preparation method thereof

    CN113308174A

  • Nanosheet composite coating as well as preparation method and application thereof

    CN113621300A

  • Waterborne epoxy anticorrosive coating for inner wall of petroleum storage tank in medium environment and preparation method of waterborne epoxy anticorrosive coating

    CN113930126A